The Influence of Transformational Leadership on Work Motivation and Work Productivity - Tarya Witarsa; Siti Musliha; Winur Asri (PT Publikasiku Academic Solution, 2026)
In the era of globalization and the Industrial Revolution 4.0, organizations face rapid changes that demand high-quality human resources and effective leadership. However, various organizational problems persist, such as weak leadership communication, lack of employee appreciation, and authoritarian leadership patterns, which lead to low work motivation and productivity. Transformational leadership is considered a strategic solution to address these issues. This research aims to analyze the influence of transformational leadership on work motivation and productivity within organizations. The method used in this study is a qualitative descriptive approach with a literature study method. Data were collected from scientific sources, including books, journals, and previous research relevant to the study topic. The results indicate that transformational leadership has a significant relationship with increased employee motivation through inspiration, individual consideration, and encouragement of innovation. Furthermore, transformational leadership also improves work productivity by fostering an effective, harmonious, and participatory work culture. Therefore, the implementation of transformational leadership in organizations is an important strategy for enhancing the quality of human resources and achieving organizational goals.